The Mass Spectra of Some of Substituted Tetrahydroquinoxaline Compounds. - RASTOGI, R.C.; BORTHAKUR , N.; Khan, R.H. (Asian Journal of Chemistry, 2010)
In the present notes, the authors have described the electron impact mass spectra of the N-substituted tetrahydroquinoxaline compounds.